Gender differences and patterns of cardiovascular risk factors in Type 1 and Type 2 diabetes: a population‐based analysis from a Scottish region. Issue 1 (25th September 2014) - Collier, A.; Ghosh, S.; Hair, M.; Waugh, N.
Abstract Aim To explore the gender differences, along with the relationships between BMI, glycaemic control, cardiovascular risk factors and the prevalence of diabetes complications, in a representative population‐based group of people with Type 1 and Type 2 diabetes. Methods Data were obtained from general practices in Ayrshire and Arran, Scotland for 15 351 patients. Results In the cohort with Type 1 diabetes, after adjustment for age, men had a significantly lower BMI (P = 0.007) and significantly lower total cholesterol (P = 0.005), HDL‐cholesterol (P = 2.5*10‐17) and HbA1c levels (P = 0.003) than women. By contrast, men had higher blood pressure, both systolic (P = 0.034) and diastolic (P = 0.0003), and higher non‐fasting triglyceride levels (P = 0.001). Men with Type 1 diabetes had a higher prevalence of neuropathy (P = 0.021). Among people with Type 2 diabetes, men had a significantly lower BMI (P = 4.26*10‐37), and significantly lower total cholesterol (P = 2.96*10‐62) and HDL‐cholesterol levels (P = 8.25*10‐141) but higher non‐fasting triglyceride levels (P = 0.0002). In Type 2 diabetes, men had a higher prevalence of ischaemic heart disease (P = 1.66*10‐25), stroke (P = 0.002) and peripheral vascular disease (P = 1.68*10‐12), while women were older (P = 4.83*10‐23), heavier and had a higher prevalence of hypertension (P = 5.32*10‐12). More people with Type 2 diabetes were on lipid‐lowering treatment (84.7 vs 52.4%; P = 5.51*10‐8) than were those with Type 1 diabetes. The prevalence of retinopathy was higher among non‐smokers thank smokers in people with both Type 1 and Type 2 diabetes (Type 1, P = 0.016; Type 2, P = 0.001). Conclusions The study shows gender differences between Type 1 and 2 diabetes that are of clinical significance and require further investigation. Follow‐up of the patients included in the present study should give us much greater understanding of the importance of gender in the development of metabolic abnormalities and diabetes complications.